(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, who gave to everything his creation, then guided, then prayers and peace be upon those whom he chose as guides. to His servants, especially the Seal of the Prophets, the Master of the Messenger and the Chosen Ones, Abu al-Qasim al-Mustafa, may God bless him and grant him peace. childbirth. God created man and provided him with the elements of the mind and the will. from falsehood, and willingly chooses what he chooses to be valid and achieve his purposes and goals. And God has made the discerning mind a proof for Him over His creation, and He has helped him with what He overflowed the minds of a source of support.